Communicating Toxicogenomics Information to Nonexperts : a workshop summary (National Academies Press, 2005)
Considers strategic for communication toxicogenomic information to the public and other non-expert audiences, specifically addressing the communication of some key social, ethical, and legal issues related to toxicogenomics and addressing how information related to the social implications of toxicogenomics might be perceived by nonexperts.